1998
DOI: 10.1103/physrevlett.80.3867
|View full text |Cite
|
Sign up to set email alerts
|

First Experimental Study of the Darrieus-Landau Instability

Abstract: This paper presents the first direct experimental measurements of the growth rate of the Darrieus-Landau instability on a planar laminar premixed flame front. Prior to measurements, the intrinsically unstable flame is maintained stable by a novel technique based on the response of the flame to an acoustic parametric forcing. The growth rates of the instability, measured when the forcing is removed, are in agreement with the theoretically predicted values. [S0031-9007(98)05920-1]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(54 citation statements)
references
References 5 publications
(8 reference statements)
6
47
1
Order By: Relevance
“…As in previous experiments with propane [19,13] the range of equivalence ratios where it was possible to measure growth rates is limited. For low equivalence ratios, we are close to the extinction limit for the Hele-Shaw cell with a gap width of 4.7mm, which probably explains the low growth rates observed for φ = 0.81.…”
Section: Experimental Results For Propane and Methane-air Mixturesmentioning
confidence: 99%
“…As in previous experiments with propane [19,13] the range of equivalence ratios where it was possible to measure growth rates is limited. For low equivalence ratios, we are close to the extinction limit for the Hele-Shaw cell with a gap width of 4.7mm, which probably explains the low growth rates observed for φ = 0.81.…”
Section: Experimental Results For Propane and Methane-air Mixturesmentioning
confidence: 99%
“…We attempt to do this in the experiments described below. Premixed flames of methane and propane are main- tained perfectly planar using a periodic acceleration field [14,24]. The flames are then subjected to a periodic pressure fluctuation at a different higher frequency.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…a density 'discontinuity') to create the unsteady RT effect. Experimental (Searby 1992;Clanet & Searby 1998;Clanet, Searby & Clavin 1999;Al-Shahrany et al 2006) and numerical (Gonzalez 1996) studies indicate that the dynamic effect of the acoustic acceleration and the DL instability are both important.…”
Section: R C Assier and X Wumentioning
confidence: 99%
“…Searby & Rochwerger 1991;Clanet & Searby 1998;Bychkov 1999;Aldredge 2005). It was shown that externally imposed sound waves with a moderate amplitude may stabilise an intrinsically unstable flat flame, but at a high enough amplitude they trigger secondary parametric instabilities.…”
Section: R C Assier and X Wumentioning
confidence: 99%